한반도 정전체제와 냉전문화 - 김귀옥; Gwi-ok Kim (한국과 국제정치, 2023)
한반도 정전협정이 체결된 지 70년이 되었다. 세계적 탈냉전으로 국경 없는 전지구화가 진행된 지 30년도 넘었다. 전지구화시대에도 한반도는 분단구조, 정전상태를 벗어나 평화체제를 수립하지 못한 채, 냉전의 섬으로 남아있다. 최근 한국의 대중문화는 세계적으로 주목을 받고 있다. 세계적으로 선풍을 일으키고 있는 한국의 대중문화 속에 한국의 냉전문화는 어떤 기제에 따라 작동하고 있는가가 궁금하지 않을 수 없다. 정치적 민주화가 제자리를 잡아가면서 한국의 반공주의는 약화하였으나, 냉전문화는 어떤 기제로 인해 여전히 힘을 발휘하고 있는 것인가? 또한, 현재 한국의 대중문화와 냉전문화는 어떤 연관이 있을까? 자본주의적 대중문화가 더 커지면 냉전문화는 약화하거나 사라질 수 있는 것인가? 이 글에서는 우선 한국의 냉전문화를 둘러싼 선행연구를 살펴보면서 냉전문화를 정의해보도록 한다. 둘째, 냉전문화를 형성하고 작동하고 있는 기제와 특징을 분석해보자 한다. 특히 냉전체제를 지지해온 냉전 지식이나 냉전지향의 법제도, 교육, 대중문화 등이 어떻게 구성되며 작동하고 있는가를 살펴보고, 마지막으로 냉전문화를 극복하기 위한 노력을 제시하면서 글을 맺고자 한다. This year marks the 70th anniversary of the signing of the armistice agreement on the Korean Peninsula. It has been more than 30 years since globalization without borders has progressed due to the global post-Cold War. Even in the era of globalization, however, the Korean Peninsula remains an island of the Cold War without establishing a peace regime outside of the divisional structure and armistice. Recently, Korean pop culture has been in the spotlight around the world. But I wonder what mechanism Korea’s Cold War culture is working under Korea’s popular culture, which makes a sensation in world culture. With the progress of political democratization, Korea’s anticommunism has weakened, but in what mechanism does the Cold War culture still exert its power? Also, how is the current Korean pop culture related to Cold War culture? Can the Cold War culture weaken or disappear if capitalist popular culture grows bigger? In this article, first of all, I try to define the Cold War culture by examining previous studies surrounding the Cold War culture in Korea. Secondly, I would like to analyze the mechanisms and characteristics that form and operate the Cold War culture. In particular, I would like to examine how the Cold War knowledge and Cold War-oriented legal systems, education, and popular culture, which have supported the Cold War system, are organized and working. Finally, I’ll present how to overcome the Cold War culture.